Antidiabetic and Hypolipidemic Effects of Different Fractions of Catharanthus Roseus (Linn.) on Normal and Streptozotocin-induced Diabetic Rats - Islam, M. A.; Akhtar, M. A.; Islam, M. R.; Hossain, M. S.; Alam, M. K.; Wahed, M. I. I.; Rahman, B. M.; Anisuzzaman, A. S. M.; Shaheen, S. M.; Ahmed, Maruf (Journal of Scientific Research, 2009)
The antidiabetic and hypolipidemic effects of petroleum-ether, ethyl acetate and chloroform fractions from ethanolic extract of the leaves of Catharanthus roseus (C. roseus) were investigated in normal and streptozotocin-induced diabetic rats (SIDRs). Single doses (150 mg/kg, i.p.) of C. roseus extracts in the fasting blood glucose (FBG) levels were determined in normal and SIDRs on 0, 1, 2, 3, 6, 10, 16, and 24th hours and serum triglyceride (TG) and serum total cholesterol (TC) levels were determined after 24th hour. In normoglycemic rats and in SIDRs, petroleum-ether and ethyl acetate fraction of C. roseus reduced blood glucose level significantly. In case of hypolipidemic effects, all fractions reduced serum total cholesterol but the ethyl acetate fraction of C. roseus was the most effective. All fractions of C. roseus reduced serum triglyceride level but the ethyl acetate fraction reduced triglyceride level at the highest. The antidiabetic and hypolipidemic activities were compared to metformin HCl (150 mg/kg). Of all the three fractions, ethyl acetate fractions were the best in activity. Ethyl acetate fraction of C. roseus was found to contain flavonoids and alkaloids. The mechanism underlying the antidiabetic activity is probably increased glycogenesis, decreased gluconeogenesis or decreased absorption of glucose from intestine. Keywords: Catharanthus roseus; Antidiabetic; Hypolipidemic; Streptozotocin-induced diabetic rat. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1075